Detection of Blotted Proteins Methods and Protocols - Kurien, Biji T.; Kurien, Biji T.; Scofield, R. Hal.; Scofield, R. Hal. (Methods in Molecular Biology, 2015)
This detailed volume provides methods and techniques for detection after blotting.  Chapters guide readers through a number of variations on the theme of protein transfer to solid support followed by detection, presenting adaptations of traditional techniques, and original methods of protein blotting. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Practical and authoritative, Detection of Blotted Proteins: Methods and Protocols presents numerous techniques based on the Western blot, providing detailed, readily reproducible methods, tips, and alternatives directly and easily transferable to the laboratory setting.